ANALISIS KEBIJAKAN PENGADAAN BARANG DAN JASA PEMERINTAH BERKELANJUTAN - Mustofa Kamal (Puslatbang KHAN, 2020)
Sustainable government procurement policies have become mandatory but there is no measurement model for policy implementation. This study aims to identify actors, models, and alternative models for sustainable government procurement policies. Qualitative research was conducted with a juridical normative approach through literature study. The results show that actors of sustainable government procurement policies are government procurement policy agencies, nine ministries, and all local governments. Implicitly, a policy model with an institutional approach is used in sustainable government procurement which has weaknesses in the form of a model for measuring the success of the policy that does not exist and communication-coordination-cooperation between institutions is still not optimal. Alternative models can be used in the form of rational and incremental approaches. The implication is that policy actors need to develop a model for measuring the success and achievement indicators of sustainable government procurement.